Preferences outgoing students of the University of the Third Age in Wabrzezno - Zielińska, Eliza Maria; Barwińska-Szczutkowska, Gabriela; Barwińska, Sylwia (Journal of Education, Health and Sport, 2016)
The article concerns to specify preferences and trends and themes tourist trips. The study included 52 students of the University of the Third Age (UTA) in Wąbrzeźno (Poland). The results showed that 35% of respondents spend free time at home. Those who participated directly in the tourist trips were in second place (28%), and the main motivation for tourist trips in the study group was the desire to explore new places and the need for climate change.